Results of Palliative Care Model in the Health Community Network, Nan Province - สุริยาทัย, จุฬารัตน์; ไชยสลี, ณัฐกฤตา; ธนะขว้าง, ชลิดา; พันธุ์แก้ว, ศิริลักษณ์; รัชตโสตถิ์, ภภัสสร; รัตนพันธ์, ปิยวัฒน์ (Journal of Health Science of Thailand, 2023)
The purpose of this action research was to develop and evaluate a palliative care model in Tha Wang Pha health community network, Nan province. It was conducted from September 2018 to October 2019. The study consisted of 3 phases: (1) problem analysis; (2) implementation, which was performed in 4 steps: planning, practice, observation & reflex on problems; and (3) evaluation. Purposive sampling was applied to recruit 32 terminal patients with late stage cancer, late stage chronic obstructive pulmonary disease, end-stage renal disease and those diagnosed with terminally ill patients from other hospitals, together with 32 caregivers. The instruments for data collection were (1) a personal data record form, (2) the palliative care model of Tha Wang Pha district health network (3) satisfaction assessment form (FAMCARE-2), (4) Edmonton Symptom Assessment System (ESAS), (5) family satisfaction assessment form for palliative care, (6) Palliative Care Outcome Scale (POS), and (7) good death assessment form. The data were analyzed and present in median and compare before and after by using Wilcoxon matched-pairs test. It was found that the average score of Palliative Care Outcome scale was significantly decreased after the implementation (p<0.05). The average score of caregivers satisfaction (FAMCARE-2) was 90.85% toward palliative care services, which was at high level; and the average score of good dead was 93.75%. In conclusion, the development and evaluation of palliative care model from Tha Wang Pha hospital for the health community network has resulted in positive outcomes of patients; and was useful for supporting terminally-ill patients and their family. Therefore, this system should be an effective model for palliative care in community hospitals.